Effectiveness of Leaflet Media in Health Education to Improve Maternal Knowledge on Implant Contraception - S, Kartini (Genius Journal, 2024)
Introduction: Health education is crucial in increasing public knowledge about reproductive health, including Family Planning. The leaflet serves as a medium for conveying information, the effectiveness of which is measured by how well the leaflet helps in better understanding implant contraception, including its benefits, risks, installation procedure, and maintenance. This increase in knowledge is then expected to encourage more accurate decision-making regarding the use of implant contraceptives. Objective: This study aims to determine the effectiveness of leaflet media in health education on increasing mothers' knowledge about implant contraception at the Kurra Health Center in Tana Toraja Regency. Method: The research design used is a pre-experiment with a one-group pre-post test design. The research population consists of all Women of Childbearing Age (WUS) in Lembang Rante Limbong, the working area of Puskesmas Kurra, totaling 131 individuals. A sample of 57 individuals was selected using a purposive sampling technique. Data were analyzed using a paired t-test or Wilcoxon test, depending on the data distribution. Result: The research results show a p-value of 0.000, which is smaller than the α value of 0.05. Conclusion: There is an effectiveness of leaflet media in health education toward increasing mothers' knowledge about implant contraception at the Kurra Health Center, Tana Toraja Regency. This increase in knowledge is expected to help WUS make wiser decisions regarding family planning and choose contraceptive methods that align with their needs and preferences.